If you have a Scientific calculator you can type this in
Let's solve your equation step-by-step.
−(1+7x)=6(−7−x)+36
Step 1: Simplify both sides of the equation.
−(1+7x)=6(−7−x)+36
−7x+−1=(6)(−7)+(6)(−x)+36(Distribute)
−7x+−1=−42+−6x+36
−7x−1=(−6x)+(−42+36)(Combine Like Terms)
−7x−1=−6x+−6
−7x−1=−6x−6
Step 2: Add 6x to both sides.
−7x−1+6x=−6x−6+6x
−x−1=−6
Step 3: Add 1 to both sides.
−x−1+1=−6+1
−x=−5
Step 4: Divide both sides by -1.
−x
−1
=
−5
−1
x=5
Answer:
x=5
Vertically opposite angles are always equal.
Given angles are (8x+12)° and (3x+37)°
=> (8x+12)° = (3x + 37)°
=> 8x - 3x = 37-12
=> 5x = 25
=> x = 25/5 = 5°
Angle 1 = (8x+12)° = (8(5)+12) = 40+12 = 52°
Angle 2 = (3x + 37)° = (3(5)+37)° = 15+37 = 52°
The answer is 6 shirts
12.5x+8=83
12.5x=83-8
12.5x=75
x=75/12.5
x=6